2010
DOI: 10.5658/wood.2010.38.2.135
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic Analysis of Reticulitermes speratus using the Mitochondrial Cytochrome C Oxidase Subunit I Gene

Abstract: Reticulitermes speratus is commonly found in Asia, including Korea and Japan. We recently analyzed the 5' region of mitochondrial cytochrome c oxidase subunit I to perform a phylogenetic analysis of R. speratus KMT1, isolated in Seoul, Korea. Our results, using COXI, suggest that the taxonomy of R. speratus should be reconsidered with regard to the subgenus group. A similar phylogenetic analysis by COXI and COXII demonstrated the reliability of COXI genetic information in a molecular phylogenetic analysis of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…The termites used were R. speratus KMT001 (Cho et al, 2010), which were collected in the Bukhan Mountain, Seoul, Korea (latitude: 37.614009, longitude: 126.990545). The termites were grown at 26°C and 70% humidity without light.…”
Section: Termitesmentioning
confidence: 99%
See 1 more Smart Citation
“…The termites used were R. speratus KMT001 (Cho et al, 2010), which were collected in the Bukhan Mountain, Seoul, Korea (latitude: 37.614009, longitude: 126.990545). The termites were grown at 26°C and 70% humidity without light.…”
Section: Termitesmentioning
confidence: 99%
“…GH18 has eight similar α/β-barrel structures and two conserved regions, which play an important role in enzymatic activity. All structure and regions are located on the β3 and β4 strands (Cho et al, 2010;Fukamizo, 2000;Henrissat and Bairoch, 1993;Korb et al, 2012;Kramer and Muthukrishnan, 1997;Sharma et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Lower termites, Reticulitermes speratus KMT001 (Cho et al, 2010b), were collected from Bukhan Mountain, Seoul, Korea; 50 worker termites were grown at 4°C, 10°C, 15°C, 22°C, and 26°C for 14 days, and their guts were extracted with tweezers (Kim et al, 2010). The termite gut was extracted at the same temperature as the growing conditions for the sample to maintain the bacterial flora.…”
Section: Purification Of Chromosomal Dna From Symbiotic Bacteriamentioning
confidence: 99%
“…It is quite interesting how termites can inhabit a variety of regions from tropical rainforests to frozen soil. Reticulitermes speratus is a termite species found in Korea (Cho et al, 2010b). It has been suggested that termites originally landed on the southern region of the Korean peninsula from Japan and migrated north (Park et al, 2006;Kim et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…However, they also serve as ecological suppliers providing various nu-trients, including nitrogen compounds (Govorushko, 2019;Lobry de Bruyn and Conacher, 1990). They are widely distributed worldwide (Bourguignon et al, 2016), including Korea with freezing temperatures in winter (Cho et al, 2010b;Kim et al, 2012). In Korea, a representative lower termite species is Reticulitermes speratus (Cho et al, 2010b;Kim et al, 2012).…”
Section: Introductionmentioning
confidence: 99%